An integrated approach for efficient conversion of Lemna minor to biogas. (15th January 2019) - Kaur, Manpreet; Srikanth, Sandipam; Kumar, Manoj; Sachdeva, Sarita; Puri, S.K.
Graphical abstract: Highlights: Biogas (CH4 + H2 ) production from L. minor by integrated approach has high potential. Three-stage integration was effective for highest energy yield (38.7 ± 1 mol/kg TOCR ). Maximum biogas recovered resulting in recycling of 530.7 dm 3 of CO2 per kg TOCR . Analysis of organic flux elucidated the effectiveness of each process on integration. Abstract: Aquatic weed, Lemna minor was evaluated for its potential as a feedstock for gaseous fuel production (biohythane) in an integrated strategy. Three approaches viz., acidogenic fermentation (HAF ), electrohydrogenesis (HMEC ) and methanogenesis (MAD ), were evaluated in single stage as well as in different combinations of two stage (HAF → HMEC, HAF → MAD ) and three stage (HAF → HMEC → MAD, HAF → MAD → HMEC ) to tap the maximum feasible energy. Compared to single and two-stage operations, three-stage operation evidenced higher biogas (H2 + CH4 ) yield with remarkable total organic carbon (TOC) reduction. Irrespective of the integration sequence, HAF in first stage depicted the possibility of harnessing higher energy by accumulation of volatile fatty acids (VFA) along with H2 production. Similarly, integration of MAD in second stage showed the possibility of tapping higher energy rather than HMEC due to higher carbon loss as CO2 coupled to more H2 fraction in biogas in case of HMEC . Among, three-stage integrations, higher biogas yield and energy recovery was observed in HAF → MAD → HMEC (38.77 mol biogas/kg TOCR ; 25, 415 KJ/kg TOCR ) as compared to HAF → HMEC → MAD (37.79 mol biogas/kg TOCR ; 15, 416 KJ/kg TOCR ). Along similar lines, analysis of organic carbon flow exhibited significant substrate degradation in three stage integrations (72.5–81.4%) as compared to second (66.2–70%) and first stage (39.7–56.5%).